(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2012)
Book review The Community Development Reader: History, themes and issues Gary Craig, Marjorie Mayo, Keith Popple, Mae Shaw and Marilyn Taylor (editors) 2007. Bristol: Policy Press